THE URGENCY OF TOTAL QUALITY MANAGEMENT IN ACADEMIC SUPERVISION TO IMPROVE THE COMPETENCY OF TEACHERS - Saihu Saihu (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
This paper discusses one way to improve teacher competency through academic supervision as a form of implementation of TQM (Total Quality Management). Academic supervision is considered to be able to provide solutions in the improvement process, as well as improving the quality of teachers in an educational institution. This paper focuses on theoretical concepts, objectives, principles, planning, and techniques in the implementation and follow-up of academic supervision. Sources of data in this paper are obtained through collecting data and information through bibliographic aids or commonly referred to as reference books. This paper uses qualitative research methodologies with applied research. The results of this paper indicate that true academic supervision can improve teacher competence in an educational institution. Of course this is supported by careful planning, also the right techniques in its implementation. However, because this academic supervision is a form of implementing TQM, it refers to one of the characteristics of TQM that is continuous improvement, it is necessary to have a follow-up as a form of continual improvement over the implementation of academic supervision that has been carried out previously by the school principal or madrasa headmaster. Thus, the results to be achieved from this implementation are improvements, as well as increasing teacher competence in an educational institution.